2001
DOI: 10.1182/blood.v97.3.608
|View full text |Cite
|
Sign up to set email alerts
|

SHP2 and cbl participate in α-chemokine receptor CXCR4–mediated signaling pathways

Abstract: Stromal cell-derived factor (SDF)-1␣ and its receptor, CXCR4, play an important role in cell migration, embryonic development, and human immunodeficiency virus infection. However, the cellular signaling pathways that mediate these processes are not fully elucidated. We and others have shown that the binding of SDF-1␣ to CXCR4 activates phosphatidylinositol-3 kinase (PI-3 kinase), p44/42 mitogen-associated protein kinase, and the transcription factor nuclear factor-B, and it also enhances the tyrosine phosphory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
59
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(64 citation statements)
references
References 77 publications
5
59
0
Order By: Relevance
“…The interaction between SHP-2 and c-Cbl has been described earlier [44,45], but effects of this interaction for T cell function has not been shown to date. Potential target molecules of SHP-2/Cbl complex in T cells that are located upstream of PKC in the TCR signal transduction cascade are CD3-e, CD3-f, Lck, ZAP-70 or in particular PI3K [52][53][54][55][56][57].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The interaction between SHP-2 and c-Cbl has been described earlier [44,45], but effects of this interaction for T cell function has not been shown to date. Potential target molecules of SHP-2/Cbl complex in T cells that are located upstream of PKC in the TCR signal transduction cascade are CD3-e, CD3-f, Lck, ZAP-70 or in particular PI3K [52][53][54][55][56][57].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, dephosphorylation of the target protein should either produce an activating signal or could lead to the inactivation of an inhibitory signal. SHP-2 is able to directly interact with the receptor CXCR4 in Jurkat cells [44], which could be mediated by an ITIM in the fourth intracellular domain of CXCR4. In Jurkat as well as in breast cancer cells, receptor stimulation leads to the association of SHP-2 with Cbl, PI3K, 14-3-3b and Crk-L [44,45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cbl acts as an adaptor protein in tyrosine-dependent signaling, and has been shown to be phosphorylated upon CXCL12 stimulation in T cells (Chernock et al, 2001). Stimulation with CXCL12 increased the tyrosine phosphorylation of Cbl in DU4475 cells (Figure 7a,upper panel).…”
Section: Cbl Regulates the Cxcl12-induced Chemotaxis And Chemoinvasiomentioning
confidence: 97%
“…There has been considerable interest regarding signaling events induced by CXCL12 that regulate chemotaxis in T cells. Our laboratory and others have shown that CXCR4 ligation leads not only to G proteincoupled receptor events but also to induction of protein tyrosine kinases of the src family, as well as to induction of the RAFTK/Pyk2 platform kinase, and protein tyrosine phosphatases in T cells (Ganju et al, 1998a;Hatch et al, 1998;Wang et al, 2000;Chernock et al, 2001;Zhang et al, 2001). CXCR4-mediated chemotactic signaling is also regulated by the nitric oxide pathway (Cherla and .…”
Section: Introductionmentioning
confidence: 96%